Polacy na Uralu w latach 60.–80. XIX wieku w świetle wspomnień Władysława Zahorskiego - Sikorska-Kulesza, Jolanta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
The article is based on a fragment of the diary of Władysław Zahorski, still in the manuscript, entitled “My memories” and rich literature on the subject. It was written down years later, therefore it should be analyzed with great sensitivity and it should be careful to formulate conclusions. The author of the diary was a well-known Vilnius doctor, cultural and social activist and the author of many works on the history and monuments of Vilnius. The article deals with the problems of exiles in Ufa, observed from the position of a child from the intelligentsia family from western Krai. The author came from a family, whose social position and material status were definitely better than those Poles who were subjected to forced exile in post-January realities. In the diary it can be found the unknown and valuable information, that complements the current state of knowledge about the life of exiles of this part of Siberia. In addition, it creates a cognitive perspective concerning the exiles in the consciousness of a generation of insurgents’ children in 1863, to which Władysław Zahorski belonged.